When the levee breaks - Mohd Azmyl, Md Yusof * (The Malaysian Insight, 2023)
AS last year’s seasonal floods were not as devastating to the Klang Valley as in the year before, people were able to usher in 2023 with events and festivities across the greater Kuala Lumpur metropolitan area. Since my experience of the 2021 floods, I have become anxious whenever I see heavy clouds in the sky. I was among the many who were stranded in Shah Alam on December 18 that year.